Ashwin defeated 55 other contestants - Norhidayah, Mohamad (2017)
UMP PhD student from Faculty of Chemical & Natural Resources Engineering, Ashwin Charles Benedict was crowned the winner for Asia-Pacific 3 Minute Thesis Competition. Ashwin defeated 55 others contestants from Australia, New Zealand and Asia.